El turismo del cantón Guano y su incidencia en el desarrollo local - Gualoto Cando, Pedro Javier (2024)
The present work aims to investigate how tourism in the Guano Canton affects local development, where tourism today is one of the main sources of income for the national and international economy, generating new jobs and activating their economies. Providing experiences and services through tourist attractions, however, despite this potential, tourism in the region faces various challenges that hinder its growth and its ability to contribute to local development, there is little information or lack of interest in how to properly manage the conservation of natural and heritage attractions that have history and reveal a little more about our culture and that are of great importance for the development of tourism activity as such. The hypothetical-deductive method has been applied which allowed to solve the hypothesis, tourism in the Guano Canton and its impact on local development, allowing the identification of the problem, statement of the problem, formulation of an isolated falsifiable hypothesis, measurement, collection and analysis of data and interpretation of the results; all, in order to test a theory. Propose strategies to reactivate the economy of the Guano canton, province of Chimborazo, which will allow the strengthening of local and tourist development through different strategies according to the needs that it presents. The study was carried out using the mixed approach since it systematically integrates quantitative and qualitative methods analyzing the current situation of the Guano canton, likewise the SWOT matrix was applied for the development of the situational diagnosis, in addition it allowed to know the reality of tourism in the Artisanal Capital of Ecuador and it was possible to determine that, based on the results obtained in the surveys applied to visitors, there is a need to create strategies that help promote and position the Guano canton as a tourist destination at the provincial, national and international level. Based on the research, the proposal to design strategies that promote tourism in the Guano canton, in order to promote local development. It is concluded that the Guano canton has countless natural attractions, however, ignorance and lack of information have prevented visitors from getting to know this magical town.